In vitro antimicrobial activities of phyllanthus amarus extract, antibiotics and their combination against leptospira interrogans - Ismail, Che Ain Munirah (2021)
P. amarus had been traditionally used in treating ailments including infectious diseases. Previous researches proved its antibacterial properties towards groups of microorganisms including Leptospira spp., but scanted. In vitro antimicrobial activity of P. amarus extracts (aqueous and methanol) and antibiotics were studied against Leptospira interrogans serovars Australis, Batavie, Canicola and Javanica. Minimal inhibitory concentrations (MIC) of aqueous and methanol extracts were determined using Ellinghausen-McCullough-Johnson-Harris (EMJH) broth microdilution method in 96-well plates, by determining the absorbance values using ELISA tray reader at 420 nm and viewed under dark field microscope after incubation of 7 days , at 30 °C and 40 rpm. Minimal bactericidal concentrations (MBC) were determined by sub-culturing Leptospira inoculum from MIC test onto EMJH solid media for two to three weeks. Synergistic testing of P. amarus extracts in combination with antibiotics were determined using checkerboard assays in the form of fractional inhibitory concentration index (FICi) values with their interpretations. The combinations with the lowest FICI values are preceded with scanning electron microscopic analysis (SEM) based on their MIC values; P. amarus extract and antibiotic against the Leptospira culture, both in singly and in combination after 18 hours of treatment at 30 °C and 40 rpm. Both aqueous and methanol extracts showed antimicrobial activity towards all tested L. interrogans serovars. MICs and MBCs ranges of aqueous extract were 100 to 400 μg/ml, and methanol extract ranging from 400 to 800 μg/ml. All tested antibiotics; ceftriaxone, doxycycline and penicillin G, exhibited antimicrobial activities with MICs and MBCs values ranging from 0.05 to 0.78 μg/ml and 0.05 to 0.78 μg/ml, 0.39 to 3.13 μg/ml and 12.5 to 25.0 μg/ml, and <0.01 to 0.78 μg/ml and <0.01 to 3.13 μg/ml, respectively. Combination of aqueous extract and antibiotic presented with indifferent effects towards Leptospira serovars with FICi values ranging from 2.24 to 2.40 for ceftriaxone, 1.59 to 3.09 for doxycycline and 2.42 to 3.41 for penicillin G. Combination of methanol extracts and antibiotics presented with indifferent effects towards Leptospira serovars with FICi values ranging from 2.51 to 3.22 for ceftriaxone, 2.82 to 3.58 for doxycycline and 2.95 to 3.38 for penicillin G. However, antagonistic effects of methanol extracts were observed in combination with doxycycline on serovar Bataviae with FICi of 4.22, and penicillin G on serovar Canicola with FICi of 4.87. SEM micrographs revealed notable changes towards the treated Leptospira cells. The combination of aqueous extract and doxycycline caused severe damages as compared to extract and antibiotic alone. Deformities observed include less coiling, thinning, shortening, less smooth with irregular surfaces, and blebbing appearances. In conclusion, P. amarus showed promising antimicrobial properties on the Leptospira spp. with aqueous extract yielded better results than methanol extract. Synergy testing revealed moderate effects even though SEM analysis presented with good findings, indicating a need for improvement in the study. As studies on plants as antimicrobial agents towards Leptospira spp. are limited, further research in this area is required.